2016
DOI: 10.1158/0008-5472.can-15-2498
|View full text |Cite
|
Sign up to set email alerts
|

SIRT2-Mediated Deacetylation and Tetramerization of Pyruvate Kinase Directs Glycolysis and Tumor Growth

Abstract: Sirtuins participate in sensing nutrient availability and directing metabolic activity to match energy needs with energy production and consumption. However, the pivotal targets for sirtuins in cancer are mainly unknown. In this study, we identify the M2 isoform of pyruvate kinase (PKM2) as a critical target of the sirtuin SIRT2 implicated in cancer. PKM2 directs the synthesis of pyruvate and acetyl-CoA, the latter of which is transported to mitochondria for use in the Krebs cycle to generate ATP. Enabled by a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(82 citation statements)
references
References 40 publications
3
78
0
1
Order By: Relevance
“…33 However, its role in glycolysis (pro or anti) remains debatable. Seong-Hoon et al found that SIRT2-lacking cells exhibited a higher extent of glycolytic phenotype in mammary tumor cells by targeting PKM2, 34 Young et al found that knockdown of SIRT2 resulted in significantly decreased OXPHOS and increased glycolysis by targeting enolase, GAPDH and aldolase in human fibroblasts. 35 In contrary, Xu et al found that SIRT2 could enhance glycolysis in A549 and MEF cells by targeting PGAM2.…”
Section: Discussionmentioning
confidence: 99%
“…33 However, its role in glycolysis (pro or anti) remains debatable. Seong-Hoon et al found that SIRT2-lacking cells exhibited a higher extent of glycolytic phenotype in mammary tumor cells by targeting PKM2, 34 Young et al found that knockdown of SIRT2 resulted in significantly decreased OXPHOS and increased glycolysis by targeting enolase, GAPDH and aldolase in human fibroblasts. 35 In contrary, Xu et al found that SIRT2 could enhance glycolysis in A549 and MEF cells by targeting PGAM2.…”
Section: Discussionmentioning
confidence: 99%
“…For example, SIRT2 deacetylates CDK9, activating its kinase activity in response to DNA replication stress (37). SIRT2 also deacetylates PKM2 and regulates its tetramerization and pyruvate kinase activity, leading to suppression of glycolysis (28). SIRT2 has been reported to deacetylate transcription factor NRF2 and regulate cellular iron homeostasis (70).…”
Section: Methodsmentioning
confidence: 99%
“…SIRT2 is an NAD + -dependent deacetylase that plays a role in multiple biological processes, such as longevity, lipid and glucose homeostasis, tumor suppression, and neurodegenerative disorders (26)(27)(28)(29)(30). Recent studies revealed the protective action of…”
Section: Sirt2 Protects Mice From Cipnmentioning
confidence: 99%
“…Compared with normal cells, cancer cells exhibit markedly upregulated glucose uptake and aerobic glycolysis, increasing the yield of biosynthetic intermediates, providing essential anabolic molecules for cell proliferation and tumor growth (Ribas et al, 2016). Gius’s study suggested that knockdown of sirtuins, a cellular energy sensor, could increase glycolytic metabolism, further promoting mammary tumor growth (Park et al, 2016). Loss of mitochondrial PTEN-induced kinase 1 (PINK1) could promote glioblastoma growth by increasing the Warburg effect in vitro and in vivo (Agnihotri et al, 2016).…”
Section: Mitochondrion As a Target Of Tigmentioning
confidence: 99%